Using next-generation sequencing technologies to develop new molecular markers for the leaf rust resistance gene Lr16 - Harrison, Nicole Rezac (Kansas State University, 2014)
Leaf rust is caused by Puccinia triticina and is one of the most widespread diseases of wheat worldwide. Breeding for resistance is one of the most effective methods of control. Lr16 is a leaf rust resistance gene that provides partial resistance at the seedling stage. One objective of this study was to use RNA-seq and in silico subtraction to develop new resistance gene analog (RGA) markers linked to Lr16. RNA was isolated from the susceptible wheat cultivar Thatcher (Tc) and the resistant Thatcher isolines TcLr10, TcLr16, and TcLr21. Using in silico subtraction, Tc isoline ESTs that did not align to the Tc reference were assembled into contigs and analyzed using BLAST. Primers were designed from 137 resistance gene analog sequences not found in Tc. A population of 260 F[subscript]2 lines derived from a cross between the rust-susceptible cultivar Chinese Spring (CS) and a Thatcher isoline containing Lr16 (TcLr16) was developed for mapping these markers. Two RGA markers XRGA266585 and XRGA22128 were identified that mapped 1.1 cM and 23.8 cM from Lr16, respectively. Three SSR markers Xwmc764, Xwmc661, and Xbarc35 mapped between these two RGA markers at distances of 4.1 cM, 10.7 cM, and 16.1 cM from Lr16, respectively. Another objective of this study was to use genotyping-by-sequencing (GBS) to develop single nucleotide polymorphism (SNP) markers closely linked to Lr16. DNA from 22 resistant and 22 susceptible F[subscript]2 plants from a cross between CS and TcLr16 was used for GBS analysis. A total of 39 Kompetitive Allele Specific PCR (KASP) markers were designed from SNPs identified using the UNEAK and Tassel pipelines. The KASP marker XSNP16_TP1456 mapped 0.7 cM proximal to Lr16 in a TcxTcLr16 population consisting of 129 F[subscript]2 plants. These results indicate that both techniques are viable methods to develop new molecular markers. RNA-seq and in silico subtraction were successfully used to develop two new RGA markers linked to Lr16, one of which was more closely linked than known SSR markers. GBS was also successfully used on an F[subscript]2 population to develop a KASP marker that is the most closely linked marker to Lr16 to date.
Keywords: wheat; RNA-seq; Lr16; RGA; KASP; genotyping-by-sequencing; Plant Pathology (0480)